An Ecologically Oriented Operation Strategy for a Multi-Reservoir System: A Case Study of the Middle and Lower Han River Basin, China. (October 2018) - Wang, Hao; Lei, Xiaohui; Yan, Denghua; Wang, Xu; Wu, Shuyue; Yin, Zhengjie; Wan, Wenhua
Abstract: Constructing and operating a multi-reservoir system changes the natural flow regime of rivers, and thus imposes adverse impacts on riverine ecosystems. To balance human needs with ecosystem needs, this study proposes an ecologically oriented operation strategy for a multi-reservoir system that integrates environmental flow requirements into the joint operation of a multi-reservoir system in order to maintain different ecological functions throughout the river. This strategy is a combination of a regular optimal operation scheme and a series of real-time ecological operation schemes. During time periods when the incompatibilities between human water needs and ecosystem needs for environmental flows are relatively small, the regular optimal operation scheme is implemented in order to maximize multiple human water-use benefits under the constraints of a minimum water-release policy. During time periods when reservoir-induced hydrological alteration imposes significant negative impacts on the river's key ecological functions, real-time ecological operation schemes are implemented in order to modify the outflow from reservoirs to meet the environmental flow requirements of these functions. The practical use of this strategy is demonstrated for the simulation operation of a large-scale multi-reservoir system which located in the middle and lower Han River Basin in China. The results indicate that the real-time ecological operation schemes ensure the environmental flow requirements of the river's key ecological functions, and that adverse impacts on human water-use benefits can be compensated for by the regular optimal operation scheme. The ecologically oriented operation strategy for a multi-reservoir system that is proposed in this study enriches the theoretical application of the multi-reservoir system joint operation which considers environmental flow requirements.